Escrita e coerência no Facebook: análise de uma experiência em sala de aula - Matheus, Claudia Marques (2014)
In this dissertation, our aim is to analyze the written coherence of Facebook posts. Based on text studies related to Textual Linguistics and also on studies related to writing in digital context, we proceed to the analysis of a compound corpus by posted comments on Facebook social network by Junior High School students, in answer to na activity that was proposed by school, considering that the involves linguistic, cognitive, cultural, social and interracial aspects, and so, it presents a large amount of implicitness in its constitution and yet considering, that coherence is related to senses production based on relation between text linguistic materiality and shared knowledge by reader and writer. The results of this survey indicate that, in writing produced on the net such as what occurs on Facebook context, the students made comments related to the activity main theme. The results indicate that, the posted messages on Facebook by students in answer to the escolar activity, the focalization of different aspects related to the theme in discussion have contributed to the maintenance and thematic progression, therefore, to the construction of net writing coherence